Application of Decision Science in Business and Management 2020
DOI: 10.5772/intechopen.87222
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Detecting the Proper Multi-Criteria Decision-Making Method Taking into Account the Characteristics of Third-Party Logistics, the Requirements of Managers, and the Type of Input Data

Abstract: The aim of the paper is to propose a framework for improving the process of choosing an appropriate multi-criteria decision-making (MCDM) method in the selection of a third-party logistics provider (3PLP). A systematic combining process was used, along with two literature reviews, one empirical survey and a case study. A four-step framework was proposed, starting with identifying common criteria that are harmonised to the 3PLP selection process, followed by analysing all aspects of the 3PLP selection problem a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In past studies, a significant contribution to science has been made in this field, which is, of course, indispensable. However, the aspect of the user of these methods was very obviously overlooked in practice, which is a matter of concern, as an e-survey [6] has shown that many companies are addressing LP selection decisions on their own. Thus, decision makers, managers, and practitioners face a great dilemma about which method to choose in decision-making problems since they do not have a deep knowledge of the methods, lack experience regarding the use of methods, and do not know all the methods available.…”
Section: Introductionmentioning
confidence: 99%
“…In past studies, a significant contribution to science has been made in this field, which is, of course, indispensable. However, the aspect of the user of these methods was very obviously overlooked in practice, which is a matter of concern, as an e-survey [6] has shown that many companies are addressing LP selection decisions on their own. Thus, decision makers, managers, and practitioners face a great dilemma about which method to choose in decision-making problems since they do not have a deep knowledge of the methods, lack experience regarding the use of methods, and do not know all the methods available.…”
Section: Introductionmentioning
confidence: 99%